The impact of job crafting intervention on nurses’ career competencies - Ehsan Hussein Gouda Magda Atiya Gaber Wafaa Mostafa Mohamed Aisha El-Sayed El-Araby (Pegem Journal of Education and Instruction, 2024)
Background: Job crafting is widely recognized as a proactive practice that empowers nurses to redefine their roles,strengthen career competencies, and accomplish professional objectives. This process contributes to both organizational effectiveness and a more meaningful, satisfying work experience for nursing professionals